Analysis of cohesive zones in cracks and slip bands using hypersingular interpolative quadratures - Korsunsky, A; Evans, J (Kluwer Academic Publishers, 2000)
A numerically efficient and fast method of solution for cracks or slip bands with a crack opening or shearing displacement-dependent cohesive stress can be developed on the basis of a Gauss-Chebyshev quadrature rule for hypersingular integrals. The resulting iterative scheme allows different 'hardening' or 'bridging' laws to be explored in a consistent manner.